PENERAPAN MODEL MISSOURI MATHEMATICS PROJECT DALAM PEMBELAJARAN MATEMATIKA MATERI SPLDV KELAS VIII SMP N 1 KAKAS - Kandouw, Lady Julia; Kaunang, Derel Filandy; Pesik, Anekke (LPPM Politeknik Saint Paul Sorong, 2024)
In learning mathematics, students' ability to solve problems affects their learning outcomes. At Smp Negeri 1 Kakas in class VIII, it was found that students' mathematics learning outcomes were still low, especially in the material of the system of linear equations of two variables, this was due to the lack of students' ability to solve mathematical problems. Therefore, the Missouri Mathematics Project model is applied in learning to solve one of the factors causing the above problems. This study aims to see student learning outcomes in learning mathematics material on the system of linear equations of two variables by knowing the average difference in learning outcomes of students who learn using the Missouri Mathematics Project learning model and those who learn using the direct learning model. This research is an experimental research that uses a quantitative approach. The samples in this study were class VIII-D as the experimental class and class VIII-A as the control class at Smp Negeri 1 Kakas in the 2023/2024 academic year. The instrument in this study was an essay-shaped student learning outcomes test. Data collection techniques through posttest results on the material of the system of linear equations of two variables in the experimental class and control class. The results of this study were obtained based on hypothesis testing using t-test statistics obtained at a significance level of 0.05 tcalculated = 2,900 and ttable = 2,010 which means H0 rejected. The conclusion of the research results is that the average learning outcomes of students who learn by using the Missouri Mathematics Project learning model are higher than the average learning outcomes of students who learn by using the direct learning model on the material of the system of linear equations of two variables.